Critical Thinking Skills of Fifth-Grade Elementary School Students in Mathematics Learning through LOC-R Model: A Descriptive Study - Mardiana, Tria; Muzayyanah, Arifah (EDUPEDIA Publisher, 2025)
Purpose - This study is aimed to describe the critical thinking skills of fifth-grade students at SD Negeri Sosrowijayan after participating in mathematics learning using the LOC-R (Literacy, Orientation, Collaboration, Reflection) model. Methodology - The study is employing a quantitative descriptive design with 20 students. The data were collected through questionnaires based on indicators, then analyzed using descriptive statistics in the form of average scores, percentages and ability categories. Findings - The result of the study revealed an average critical thinking score of 85,2 (high category), The highest-scoring indicator was connecting concepts (88%), while the lowest was identifying problems (79%). Novelty - This study integrated LOC-R model to mathematics learning in elementary school and assess its impact to eight specific indicator of critical thinking. Significance - The finding of the study provide evidence that implementation of LOC-R model is effective in enhancing students’ critical thinking, making it an alternative mathematics teaching strategy for fostering 21st-century competencies.